Development of air quality monitoring system in closed environment - Bochen Li; Xibo Ding; Qingyao Cai (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
For closed environment, the characteristic is that the confined space is small and it doesn't flow with the outside world, it will produce nausea, dizziness, weakness and other symptoms if one stayed in that environment for long time. For this, developing a monitoring system of air quality in closed environment has theoretical significance and great value. In this paper, a modular design method is used to design a closed air quality monitoring system, The air quality monitoring system is composed of a main board and detection modules. When the measured closed environment is changed, it is only necessary to add or reduce the corresponding detection module, which increases the flexibility of the system and the convenience of later maintenance, and evaluation algorithm based on fuzzy mathematics is established. The measurement and air quality evaluation experiments are carried out using the developed monitoring system, The results show that the air quality evaluation algorithm can effectively evaluate the environmental air quality, and the measurement accuracy of the environmental parameters can meet the relevant standards.